10.1016/s1541-9800(08)70577-5 (CrossRef Listing of Deleted DOIs, 2000)
PURPOSE: The purpose of this study was to report minimum 10-year survivorship, patient-reported outcomes (PROs), clinically significant outcome achievement and predictors of outcomes and failure in patients with structurally stable femoroacetabular impingement syndrome (FAIS) who underwent primary hip arthroscopy with interportal capsulotomy without capsular repair. METHODS: A retrospective review was conducted of patients undergoing primary hip arthroscopy for FAIS from 2010 to 2013 with a minimum 10-year follow-up. Exclusion criteria included hip dysplasia, Tönnis Grade >1, prior ipsilateral hip surgery and unavailable preoperative radiographs. All patients underwent interportal capsulotomy without capsular repair. Outcomes included modified Harris Hip Score (mHHS), Nonarthritic Hip Score (NAHS), minimal clinically important difference (MCID) achievement, survivorship and predictors of PROs and failure. RESULTS: A total of 150 patients were included (62.7% female), with mean follow-up of 11.7 ± 1.1 years and mean age of 38.3 ± 12.1 years. Ten-year survivorship was 90.7%; 7 patients (4.7%) underwent total hip arthroplasty and 7 (4.7%) underwent revision arthroscopy. mHHS improved from 52.0 ± 11.7 to 87.9 ± 16.7 (p < 0.001), and NAHS improved from 49.5 ± 11.4 to 86.2 ± 18.0 (p < 0.001). Patient Acceptable Symptom State (PASS) was achieved by 76.0% of patients for mHHS and 65.3% for NAHS. Female sex and higher body mass index (BMI) were associated with worse 10-year PROs, whereas Tönnis Grade 1 (p = 0.003) and lower preoperative NAHS (p = 0.034) were associated with failure. CONCLUSION: Primary hip arthroscopy for structurally stable FAIS performed with interportal capsulotomy and without capsular repair demonstrated favourable 10-year outcomes, high PASS achievement and 90.7% survivorship. Clinically, these findings provide long-term benchmarking data for counselling appropriately selected patients with structurally stable hips. Higher BMI and female sex were associated with worse 10-year PROs, while Tönnis Grade 1 and lower preoperative NAHS were associated with increased failure risk, supporting their use in preoperative risk stratification and shared decision-making. LEVEL OF EVIDENCE: Level IV, retrospective case series (single-surgeon, without comparison group).